Cognitive trajectories during the menopausal transition - Than, Stephanie; Moran, Chris; Beare, Richard; Vincent, Amanda; Lane, Emma; Collyer, Taya Annabelle; Callisaya, Michele L.; Srikanth, Velandai (Frontiers in Dementia, 2023)
Aims Female sex is associated with an increased prevalence of dementia. Menopause may have a role to play in explaining sex differences in cognition, and possibly the risk of future dementia. We aimed to determine if the rate of cognitive decline differed between stages of the menopausal transition. Materials and methods Women with data on menopause and longitudinal cognitive function from the UK Biobank study were stratified into three groups: premenopausal, perimenopausal and postmenopausal. We studied associations of these menopause groups with rate of change in reaction time, verbal-numeric reasoning, prospective memory, visual memory and attention/working memory, adjusted for age, education, ethnicity and APOEε4 genotype. We also explored the effect of menopausal hormonal therapy (MHT) use and cross-sectional brain magnetic resonance imaging (MRI) volumes on these models. Results We included 15,486 women (baseline mean age 52 years) over a mean duration of 8 years. An interaction between menopausal group status and time was found for reaction time (p < 0.01). Compared with premenopausal women, the rate of increase (worsening) in reaction time was least in postmenopausal women (β = −1.07, p for interaction = 0.02). In general, compared with premenopausal women, perimenopausal and postmenopausal women had overall poorer performance in fluid intelligence and memory over the study duration, with no difference in rates of change. The models were unaffected by MHT use and brain volume measures. Conclusions Perimenopause and post-menopause are associated with cognitive changes. Psychomotor speed appears to be most sensitive to the menopause transition, whereas other cognitive functions may be less susceptible. More sensitive structural or functional brain imaging may be required to understand the underlying neural basis for these findings.